Understanding the Issues of Coparenting in Indonesia - Jenny Lukito Setiawan; Jessica Christina Widhigdo; Amanda Teonata; Lisa Indriati; Mychael Maoeretz Engel (Journal of Educational, Health and Community Psychology, 2022)
Family plays an important role in children’s growth and development. The mechanism of co-parenting is empirically proven to have an impact in marital relationship and child development. However, the number of empirical studies on co-parenting in Indonesia is still very limited. The purpose of this study is to examine the issue of co-parenting among parents in Indonesia and to understand ways to develop effective co-parenting. This study uses a qualitative method approach. The data collection method used in this study is focused group discussion to 30 participants, including 15 fathers and 15 mothers. The study found that imbalances in the division of roles between partners and the difficulties in finding agreements are the biggest challenges for fathers and mothers. This study also found that there are four factors to implement an effective co-parenting, which are discussion, agreement in task division, giving appreciation, and good parenting references.